The Effect of Modifying Vegetable Side Dishes on The Taste and Acceptability of Food in Patients with a Regular Food Diet in The Morning Meal Menu - febi putri moleka (Jurnal Gizi Prima (Prime Nutrition Journal), 2025)
Background: The amount of leftover food measures the accomplishment of food service. High food leftovers are defined as leaving more than 25%. High food leftovers result in inadequate nutritional intake and a wasted hospital budget, hence the need for modification. Based on preliminary research conducted on Friday, March 8, 2024, on 10 patients with a regular diet, the average leftover vegetable side dish (tempeh stew) was 38.93%, with breakfast having the highest leftover percentage. The taste variable was measured using a taste questionnaire, and acceptability was measured using food weighing.Research Methods: This research is pre-experimental. The research design was a one-group pretest-posttest conducted at the Az-Zahra Hospital from May 30 to June 3, 2024. The sampling technique was purposive sampling. The sample consisted of all Class III patients on a regular diet, totaling 72 respondents. Bivariate analysis used the Gamma test for taste and acceptability variables in this research.Research Result: The results showed that there is an effect of vegetable side dish modification on taste and acceptability in the aspect of (Color) with (p-value 0.001), (p-value <0.05). (Texture) with (p-value 0.007), (p-value <0.05). (Aroma) with (p-value 0.001), (p-value <0.05). However, there was no effect on (Shape) with (p-value 0.707), (p-value >0.05). No impact on (Taste) with (p-value 0.463), (p-value >0.05).Conclusion: Based on the research results, it can be concluded that vegetable side dish modification affects the taste and acceptability of food. Az-Zahra Hospital is expected to Be able to apply the modified recipes with more variations in shape and taste.